Triptolide Induces Leydig Cell Apoptosis by Disrupting Mitochondrial Dynamics in Rats - Lv, Linyan; Chang, Yajie; Li, Yanqing; Chen, Haicheng; Yao, Jiahui; Xie, Yun; Liang, Xiaoyan; Yang, Xing; Zhang, Min; Liu, Guihua (Frontiers in Pharmacology, 2021)
Triptolide is widely used in the clinical treatment of various diseases. Side effects, including reproductive toxicity to male patients, limit its application. However, no detailed mechanisms or potential intervention targets have been reported. In this study, we show that triptolide activated the mitochondrial apoptosis pathway in rat testicular Leydig cells and induced apoptosis both in vivo and in vitro, which may cause hypoleydigism and impair spermatogenesis. Mechanistically, triptolide-induced dynamin-related protein 1 (Drp1) overexpression, which interfered with mitochondrial dynamic stability to activate the mitochondrial apoptosis pathway. Mdivi-1, a selective Drp1 inhibitor, partially reversed the mitochondrial dynamic disturbance and rat testicular Leydig cell apoptosis induced by triptolide. Inhibiting Drp1 over-activation may be a new strategy for mitigating the reproductive toxicity of triptolide.